Persepsi Dan Keterampilan Guru Dalam Mengintegrasikan Higher Order Thinking Skills (HOTS) Dalam Pembelajaran Ipa Di Smp Negeri 4 Siak Hulu - Gita Septi Rahmadwi; Iffa Ichwani Putri; Nurkhairo Hidayati (Jurnal Ilmu Pendidikan Biologi dan IPA, 2026)
This study aims to describe science teachers’ perceptions and skills in integrating Higher Order Thinking Skills (HOTS) in science learning at SMP Negeri 4 Siak Hulu. The study employed a descriptive approach using a mixed methods design. The research subjects consisted of five science teachers. Data were collected through closed-ended questionnaires and semi-structured interviews. Questionnaire data were analyzed using descriptive quantitative techniques by calculating percentages, while interview data were analyzed descriptively using a qualitative approach to support and strengthen the quantitative findings. The results indicate that teachers’ understanding of HOTS is categorized as very good with a percentage of 95%, teachers’ attitudes toward HOTS are categorized as very good with a percentage of 90%, teachers’ skills in planning and implementing HOTS-based learning are categorized as good with a percentage of 85%, and the evaluation of HOTS-based learning is categorized as very good with a percentage of 88%. The interview results reveal that teachers understand HOTS as higher-level thinking skills involving analysis, evaluation, and the application of concepts, and they consider HOTS to be important in science learning. However, teachers still encounter several challenges in implementing HOTS, such as differences in students’ abilities, limited facilities, and the availability of supporting learning materials. Based on these findings, it can be concluded that science teachers have demonstrated good perceptions and skills in integrating HOTS into science learning. Nevertheless, continuous improvement and institutional support are still required to optimize the implementation of HOTS in classroom practice.